Initial Attributions and Information-Seeking by Superiors and Subordinates in Production Variance Investigations - Harrison, Paul D.; West, Stephen G.; Reneau, J. Hal (The Accounting Review, 1988)
[Behavioral aspects of production variance investigations have been the focus of several recent articles. This research reports on a field experiment designed to obtain empirical evidence concerning the initial attributions made by a superior and a subordinate upon the occurrence of an unfavorable variance, as well as the processes they utilize when testing their initial attributional hypotheses. Evidence indicated that superiors made initial attributions that were internal relative to the subordinates, and also tended to seek additional information which was internal relative to the subordinates. This observed confirmatory hypothesis testing procedure is consistent with other research in non-accounting related settings. Implications for the design of accounting information systems are briefly discussed.]